Засади творення сучасної української візантології: кілька міркувань з огляду на сучасний стан дисципліни - Домановський, А.М. (Харківський національний університет імені В. Н. Каразіна, 2004)
The article is dedicated to the problems of a becoming of the modern Ukrainian science about a history of Byzantium. The main problems with which it collides at a stage of the becoming emerge, and ways of their solution are offered. It is offered to consider the Ukrainian science about Byzantium to be a successor of Russian pre-revolutionary and Soviet Byzantium Studies, and to save the best traditions of this science. Necessity of study of a creative heritage of scientists – Byzantinists who lived and worked in terrain of Ukraine is obvious. The acute requirement for increase of quantity of issuing in the Ukrainian tongue, dedicated study of a history of Byzantium, and also improvement of their quality is marked. Separately the problem on building Byzantine studies nomenclatures in the Ukrainian tongue is sharpened also. It is concluded, that the nomenclature on a history of Byzantium in the Ukrainian tongue should be built on the basis of the system of reading offered by Reihlin, instead of Erasmus. It is stipulated by that what exactly Reihlin`s system is oriented on Byzantium pronunciation whereas Erasmus` system it conventional in classical philology. Besides it corresponds to traditions of the Ukrainian tongue.
Keywords: візантиністика; візантологія; історія Візантії; наукова дисципліна; Україна; сучасний стан